2014
DOI: 10.1080/08927014.2014.906584
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the antifouling properties of cold-spray metal embedment using loading density gradients of metal particles

Abstract: Particles of copper, bronze and zinc were embedded into a polymer using cold-spray technology to produce loading density gradients of metal particles. The gradients were used to identify the species with the highest tolerance to the release of copper and zinc ions. The gradients also established the minimum effective release rates (MERRs) of copper and zinc ions needed to prevent the recruitment of fouling under field conditions. Watersipora sp. and Simplaria pseudomilitaris had the highest tolerances to the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…In [4] copper embedded into nylon with a depth of 40μm and a surface coverage of 60% provided AF protection for approximately 181 days. Comparing to other tests [10] in which only surface coverage was reported, a 12 weeks AF protection is potentially generated by the coatings produced in this study. By a way of comparison, soluble matrix paints used on boat hulls last for 12-15 months at the most.…”
Section: Process Window and Performance Predictionmentioning
confidence: 94%
“…In [4] copper embedded into nylon with a depth of 40μm and a surface coverage of 60% provided AF protection for approximately 181 days. Comparing to other tests [10] in which only surface coverage was reported, a 12 weeks AF protection is potentially generated by the coatings produced in this study. By a way of comparison, soluble matrix paints used on boat hulls last for 12-15 months at the most.…”
Section: Process Window and Performance Predictionmentioning
confidence: 94%
“…It has been reported that copper is a broad spectrum biocide. Copper‐based materials are always harmful to marine microorganisms, such as bacteria and diatom . Therefore, copper and copper‐based coatings are the most commonly used broad‐spectrum antifouling layers.…”
Section: Introductionmentioning
confidence: 99%
“…Copper-based materials are always harmful to marine microorganisms, such as bacteria and diatom. 11,12 Therefore, copper and copper-based coatings are the most commonly used broad-spectrum antifouling layers. Previous work demonstrated that copper-based materials possessed excellent antibacterial property, and the diatom was sensitive to copper ions released from copper-based coatings.…”
mentioning
confidence: 99%
“…Using the WC-Co coatings, the service life of these turbines may be higher due to the wear resistance offered by the coating 1 . The CGS coatings show corrosion and wear resistance but the technique can produce functionality surfaces as well, for example, photocatalytic 42 and coatings with antifouling activity 119,120 . The photocatalytic activity and the microstructure of ECTFE polymer composite coatings and C-TiO 2 nanoparticles deposited onto an epoxy resin by low pressure cold gas spraying (LPCGS) was investigated by Robotti et.…”
Section: Applications Of Cgs Technologymentioning
confidence: 99%
“…It consists in the spraying of a feedstock material onto surfaces with low thermal or electric conductive to improve it is characteristics or bring some functionality to the surface 119,120 . Highdensity polyethylene (HDPE) used in boats parts was metalized by CGS process and has shown excellent antifouling properties.…”
Section: Applications Of Cgs Technologymentioning
confidence: 99%